Optimization for Kinetic Model of Oxidative Desulfurization of Sour Naphtha Over a Natural Base Zeolite Catalyst in a Three Phase Oscillatory Baffled Reactor - Gheni, Saba A.; Hmood, Hassan M.; Ahmed, Safaa. M. R.; Mohammed, Mohammed H. (Journal of Petroleum Research and Studies, 2023)
The oxidative desulfurization (ODS) of Iraqi sour naphtha was studied in a novel design of a heterogeneous catalytic reactor. Molecular oxygen was used as an oxidizing agent and a clay-based zeolite was used as a catalyst. The present work of ODS was conducted in a three-phase oscillatory baffled reactor under different operating conditions; temperature =25, 35, 45, and 55°C, residence times (1 – 14 min), Reynold number of oscillation (175, 235, 315), and net flow Reynolds number (25, 50, 75). A zeolitic base ODS catalyst was prepared and applied as a heterogeneous catalyst in the OBR unit. The aim of this study is to obtain the ODS kinetic parameters and concentration profile of the sulfur compounds in the naphtha cut. The model developed was based on the properties of the feedstock, characteristics of the catalyst, and operation conditions inside the OBR according to the experimental observations. To obtain the kinetic model parameters mass transfer and flow conditions were applied in the model network. The equations were employed in gPROMS software to simulate the experimental results of sulfur concentration remaining after completion of the ODS process. The set of equations was successful in simulating the experimental results with a 5% absolute error. The predicted data were used for optimizing the kinetic parameters to get the ODS kinetic parameters based on minimizing sulfur concentration.